A global map of the ocean's climate. (21st May 2013) - Schultz, Colin
Abstract : Drawing on a massive set of ocean observations, Schmidtko et al . designed and built a map of the climate of the upper ocean, charting the regional properties in temperature and salinity for the global ocean. The authors' map takes aspects of ocean physics into account to better detail the ocean's properties from the surface down to where the pressure hits around 1950 decibars. The authors' map has a horizontal grid resolution of 0.5 degree and covers all the Earth's oceans, from the Southern Ocean to the Arctic Ocean.